2010
DOI: 10.1161/strokeaha.109.576611
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Study of Behavior Immediately After Transient Ischemic Attack and Minor Stroke in 1000 Consecutive Patients

Abstract: on behalf of the Oxford Vascular StudyBackground and Purpose-Most guidelines now recommend that patients with minor stroke or high-risk transient ischemic attack (TIA) are assessed within 24 hours of their event, but the feasibility of this depends on patients' behavior. We studied behavior immediately after TIA and minor stroke according to clinical characteristics, patients' perception of the nature of the event, and their predicted stroke risk. Methods-In a population-based study in Oxfordshire, UK, with fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 31 publications
8
63
2
3
Order By: Relevance
“…The results of our study are consistent with those of previous studies. 3,5,8 Two reports using data from the Oxford Vascular Study 3,5 demonstrated that patients with motor weakness, speech disturbance, and symptom duration >60 minutes were less likely than other patients to delay in seeking medical attention. Patients with a higher predicted stroke risk were more likely to act quickly due apparently to the influence of weakness and prolonged symptom duration on behavior, although there was no association between the recognition of symptoms and the urgency of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our study are consistent with those of previous studies. 3,5,8 Two reports using data from the Oxford Vascular Study 3,5 demonstrated that patients with motor weakness, speech disturbance, and symptom duration >60 minutes were less likely than other patients to delay in seeking medical attention. Patients with a higher predicted stroke risk were more likely to act quickly due apparently to the influence of weakness and prolonged symptom duration on behavior, although there was no association between the recognition of symptoms and the urgency of action.…”
Section: Discussionmentioning
confidence: 99%
“…Although the behavior of patients after stroke has been studied extensively since the advent of thrombolysis and other potential treatments, little information is available on the behavior of patients after TIA, except for the Oxford Vascular Study. [3][4][5] We investigated the factors associated with the time from symptom onset to arrival at a stroke center (onset-to-door time [ODT]) in patients with TIA admitted to stroke centers using data from a multicenter, retrospective study.…”
mentioning
confidence: 99%
“…All patients were reassessed during the 6 months follow-up, and were classified as "no symptoms or minor symptoms" (score 0 or 1), "lifestyle restriction" [2] [3], "dependent" [4] [5] according to the stroke-related handicap scale [11], and "death" [6] in our study. The follow-up information was gathered by the same neurology specialist, who conducted inquiries by phone.…”
Section: Outcome Evaluationmentioning
confidence: 99%
“…With magnetic resonance imaging (MRI) advances, several epidemiological studies have reported that the incidence of minor ischemic stroke (MIS) is up to 55% -74% in metropolitan regions [1] [2], showing MIS is a common ischemic stroke appearing in world regions. In such studies, small stroke or lacunar stroke was usually considered favorable short-term outcome and having had a very low NIHSS score, so this is why it is considered a MIS [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…29 As their neighbors across the pond have experienced, one of the primary reasons for this low rate of thrombolytic therapy is the lack of an urgent response when stroke symptoms are noted by patients or witnesses. [30][31][32][33] Some of the factors that contribute to this delay include the following:…”
Section: Factors Thwarting Provision Of Timely Therapymentioning
confidence: 99%